UJI EFEKTIVITAS EMPAT VARIASI PROPOLIS TRAP TERHADAP PRODUKSI PROPOLIS LEBAH MADU Apis mellifera L. (PERENNIAL, 2006)
The propolis produced by honeybees as it is used a material for cosmetic and health industry fiberglass-constructed has high economy value. However, the effective methode for the propolis production has not been found. The objective of this research was to find out the effectiveness of four propolis traps variations on the propolis production of Apis mellifera honeybees. Materials used in this research were sixteen colony of Apis mellifera honeybees and propolis traps. The propolis production and the formed surface area on traps were collected from four trap treatments with four replications. The obtained data were analyzed by using Completely Random Design Analysis and Tukey Test. The most effective of propolis traps was that made of fiberglasses with hole direction same as frame direction (the average production of 2.03 g). The largest of propolis surface area was produced by propolis trap with hole direction same as frame direction (28.29 cm2). No corellation between the large of propolis survace (cm2) and propolis production (g) was observed.Keywords: honeybees, propolis traps, propolis production.